THE TEACHERS’PERSPECTIVEON CULTURAL CONTENT IN INDONESIAN SECONDARY SCHOOL ENGLISH TEXTBOOK - Budianto, Safira Nur Fatiha (Journal of English Teaching and Learning, 2024)
This research is aimed at investigating what cultures are dominantly presented in English textbook used by Junior High School students grade VII in Banyuwangi, entitled “English for Nusantara for Grade VII” and how they are presented. The data were collected from the analysis of the textbook, interview, and questionnaires distributed to three English teachers. The method used in this study is document analysis. Some underlying models proposed by Cortazzi and Jin (1990) and Yuen (2011) were used as the main framework for analyzing the textbook. The investigation revealed two main facts. Firstly, Source culture, Target Culture and International Culture are presented in imbalance proportion. Source culture, in the forms of tangible products such as naming, places, and food, are the most dominant cultural content. Secondly, most of the teachers agree that the practice of cultural aspect should appear the most instead of the product since the practice can include of the moral values of culture. The findings of this study may encourage material developers to take into account cultural aspect which are beneficial for English learners in ELT materials for their future design.